Antidepressant use and off-label prescribing in primary care in Spain (2013-2018) - Cristina Espín Martínez; Diego Pablo Sánchez Martínez; Julián Jesús Arense Gonzalo (Elsevier, 2022)
Introduction: Recent studies show an increase in the use of antidepressants in minors (younger than 18 years), although few antidepressants are indicated for this age group. The aim of our study was to calculate the annual prevalence of antidepressant use in children and adolescents and to review the adherence of prescription to current indications. Methods: Study of the prevalence of antidepressant use in minors based on the records of the Electronic Database for Pharmacoepidemiologic Studies in Primary Care (BIFAP) of Spain for the 2013-2018 period, considering at least one prescription per year for each patient. Results: The prevalence of antidepressant prescription in patients from the BIFAP cohort increased between 2013 (7.97 prescriptions per 1000 patients) and 2018 (8.87 prescriptions per 1000 patients), in most groups and in both sexes. In this period, female patients received the most prescriptions, surpassing prescriptions in male patients by up to 2.5 points in the overall rates. In patients younger than 13 years, this trend was inverted and antidepressant use was higher in male patients. The prevalence of prescription rose with increasing patient age, as did the proportion of off-label prescriptions. The use of off-label medication decreased over time. Conclusions: There was a gradual increase in the prevalence of antidepressant prescription in minors younger than 18 years, with a predominance of the female sex. The high proportion of unapproved medication use in this age group calls for more thorough investigation of the risk-benefit balance of these treatments and of safer treatment alternatives. Resumen: Introducción: Estudios recientes muestran un aumento del uso de antidepresivos en menores de 18 años aunque pocos de ellos cuentan con indicación en este grupo de edad. El objetivo de este estudio es calcular la prevalencia anual del uso de antidepresivos en niños y adolescentes y revisar la adecuación de la prescripción a las indicaciones actuales. Métodos: Estudio de prevalencia de la utilización de antidepresivos en menores de 18 años a partir de los registros de la Base de datos para la Investigación Farmacoepidemiológica en Atención Primaria (BIFAP) durante el periodo 2013-2018, considerando al menos una prescripción por año para un mismo paciente. Resultados: La prevalencia de prescripción de antidepresivos entre los pacientes de la cohorte BIFAP ha aumentado de 2013 (7,97 prescripciones/1000 pacientes) a 2018 (8,87 prescripciones/1000 pacientes) en la mayoría de los grupos y en ambos sexos. El sexo femenino suma la mayoría de las prescripciones, superando al masculino en hasta 2,5 puntos en las tasas generales. En menores de 13 años la tendencia se invierte y los antidepresivos predominan en los chicos. La prevalencia de las prescripciones aumenta con la edad de los pacientes, igual que la proporción de tratamientos fuera de ficha técnica. El empleo de fármacos sin indicación disminuye con el transcurso del tiempo. Conclusiones: Observamos un aumento gradual en la prevalencia de prescripción de antidepresivos en menores de 18 años, preponderante en el sexo femenino. La elevada proporción de uso de estos fármacos sin indicación autorizada, exige profundizar en el balance beneficio-riesgo y en alternativas de tratamiento más seguras.